(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The e-government efforts were implemented in all of district and subordinate courts preceding to the COVID-19 issue. With the help of Information and Communication Technology and the online world, E-courts systems were created to make judging easier, clearer, and less expensive for everyone. The E-courts Services mobile app was developed in 2017, much before the COVID-19 crisis.It’s important to remember that before COVID-19, there was never a hurry to use technology in India’s justice system, and the court had purposefully turned down it. However, even before COVID-19, the judiciary was split regarding the merits or propriety of using video conferencing in court proceedings, even though technology had been around for some time.The authors have discussed a aspects of the e- court system in the slump that the Indian experienced while imposing law and order.